Helper T Cell 17 and Regulatory T Cell Levels in Peripheral Blood of Newly Diagnosed Patients with Autoimmune Thyroid Disease: A Meta-Analysis - Chen, Aizhi; Huang, Liang; Zhang, Liqin (Hormone and Metabolic Research, 2022)
This article aims to explore associated immune indicators of autoimmune thyroid disease (AITD) through a meta-analysis of published case-control studies on newly diagnosed AITD patients, intending to provide some suggestions for research on the mechanisms of AITD. Six electronic databases were searched for case-control studies on newly diagnosed AITD patients from inception to August 15, 2022. A random-effects model was used to calculate the standardized mean difference (SMD), odds ratio (OR), and 95% confidence interval (95% CI). A total of 26 articles were included in this meta-analysis. Patients with newly diagnosed AITD had higher levels of helper T cell 17 (Th17) (Hashimoto’s disease (HT): SMD=2.35, 95% CI: 1.98, 2.72; Graves’ disease (GD): SMD=1.61, 95% CI: 1.23, 1.98), lower levels of regulatory T cell (Treg) (HT: SMD=–2.04, 95% CI: –2.67, –1.42; GD: SMD=–1.35, 95% CI: –2.11, –0.58), and lower levels of forkhead box P3 (FoxP3) mRNA (HT: SMD=–2.58, 95% CI: –3.12, –2.05; GD: SMD=–2.13, 95% CI: –2.56, –1.70), compared to the healthy population. In addition, the single nucleotide polymorphism rs3761548 and rs3761549 in the promoter region of FoxP3 showed a higher frequency in the comparison of genotype “CT” only in HT patients than in the healthy population (OR=1.66, 95%CI: 1.18, 2.34). In patients with newly diagnosed AITD, the Th17/Treg ratio imbalance may develop AITD. Monitoring Th17 and Treg levels may become an essential tool to assess the organism’s immune homeostasis and hopefully guide clinical diagnosis and treatment.
Keywords: Hashimoto’s disease; Graves’ disease; helper T cell 17; regulatory T cell; meta-analysis